Milk instability associated with milk composition and seasonal lactation in grazing dairy cows - Ferrari, Claudia Gabriella Barchiesi; Salinas, Pamela Alejandra Williams; Garrido, Sonia Ilse Salvo (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to characterize dairy herds which presented positive result for alcohol test in milk showing no acidity; and to compare them to a dairy herd with negative result for same test, considering the seasonal effect. Four dairy milk herds were studied (three positives to alcohol test and one with negative result). Milk samples were collected during 3 months in winter season (season 1) and 3 months in summer lactation (season 2) for 2 years. A subsample of the diets were prepared and submitted to proximal analysis for ME content, Ca, P, Mg and K. Milk subsamples were analyzed for protein, lactose, Ca, Mg, P, pH, alcohol test, titratable acidity and proteasic activity. In cases negative to alcohol test, a high correlation index with milk crude protein, diet crude protein, milk phosphorus and lactose were observed. Dairy herds positive to alcohol test were highly correlated with lower dry matter content and a high content of crude fiber, besides these herds presented lower milk protein concentration. It was possible to notice an effect of feeding management in the instability of the milk. Summer's lactations under feeding stress condition would present milk instability.